Islam, Democracy, and Cosmopolitanism: By Ali Mirsepassi and Tadd Graham Fernée (New York: Cambridge University Press, 2014. 225 pages.) (American Journal of Islam and Society, 2015)
Ali Mirsepassi and Tadd Graham Fernée introduce their book as a “criticalstudy of citizenship, state, and globalization in societies historically influencedby Islamic traditions and institutions” (p. 1). They place their approach in theframework of the relationships between individuals and the state, religion, andpolitical community as part of investigating the democratic aspirations of Islamicsocieties. These relationships are then contextualized in a global settingwherein such aspirations presumably interconnect with some “cosmopolitanideal.”The book’s main thrust is quite clear from the outset in light of the authors’two grounding assumptions: In order to attain agency and freedom humanityin general, but Muslims in particular, must (1) respect the “core Enlightenmentvalues” of human equality and dignity regardless of ethnicity, religious affiliation,and belief or disbelief and (2) acquire a spatial vision of democracy thatincorporates “the cognitive-imaginative resources of a multidimensional Islamicheritage” (p. 1). In short, an approach in which an overarching and universalEurocentric value structure that respects Islam would help deconstructany essentialist framework that posits the latter and Enlightenment as dichotomousopposites. This could be done through a “global ethic of reconciliation”– an alternative to the “death of epistemic universalism” (p. 30) along JohnStuart Mill’s depiction of barbarian races in their failed relations to liberty –that sociologically interconnects three domains of a specific spatial-temporalcontext of Islamic practices, the democratic social virtue of nonviolence, andthe cosmopolitanism of universal and shared human values (p. 4).The authors’ analytical framework integrates three strands of twentiethcenturycritical thought concerning democratic nation-building. These pertainto John Dewey’s “conceptual pluralism,” Edmund Husserl’s “lifeworld” and“temporal Horizons,” and Amartya Sen’s conception of cultural variabilityand freedom as “capabilities” (p. 5). This is articulated within what Mirsepassiand Fernée designate as a “Pragmatic Revolution” that perceives an “unthoughtconjuncture between the Jasmine Revolution” – the so-called ArabSpring – and these critical strands’ gaining ground in western thought (p. 3).This is done through the tripartite problematic of “embededness,” “embodiment,”and the “unthought” (p. 7), all of which point to a new, even if inadequately,“theorized cosmopolitan horizon” (p. 7). The goal is to understandthe “Jasmine Revolutions” as new popular forms of mobilization that respondto a specific pattern of the modern experience, while asking the question of ...